Evolusi darwinism vs penciptaan manusia dalam perspektif Islam - Maisaroh, Putri Nur Kholishoh (Maliki Interdisciplinary Journal, 2024)
With the publication of the theory of evolution by Charles Darwin, it gave rise to a lot of criticism and debate among scientists. One of the most prominent and influential criticisms in the world is the theory of creation by Harun Yahya. When viewed from various angles, these two theories both have their own pros and cons. From the point of view of the theory of creation, there are those who do not agree with it, namely from among the evolutionists, they are trying to find scientific evidence to prove that the theory of evolution by Charles Darwin is true, even though they have not found it. Likewise, from the side of the theory of evolution, many people have reviewed it and found that the theory of evolution has not found any scientific truth.